Analisis Peran Guru Dalam Meningkatkan Motivasi Belajar Matematika Siswa pada Materi Bagun Datar Kelas VII SMP Negeri 6 Sengah Temila - Friska, Novia Rosenta; Tupulu, Nasri (Papanda, 2025)
This study aims to describe the role of teachers in enhancing the mathematics learning motivation of Grade VII C students at SMP Negeri 6 Sengah Temila on the topic of plane geometry. The study is based on the issue of low student motivation, classroom inactivity, and a lack of confidence in mathematics. Teachers are not merely content deliverers but also facilitators who create an engaging learning environment and encourage student participation. This is a qualitative and descriptive study. The research subjects consist of one mathematics teacher and six students selected purposively based on high, moderate, and low levels of learning motivation. Data collection techniques include observation, interviews, and questionnaires. The results of the study show that the teacher has carried out an essential role by creating a positive learning atmosphere, relating the material to real-life contexts, using varied and creative teaching methods, and providing reinforcement and appreciation to students. Although most students showed increased learning motivation, some still felt neglected or did not receive an appropriate learning approach. Therefore, more adaptive and personalized teaching strategies are needed to optimally motivate all students. This study is expected to contribute to helping teachers develop more effective instructional approaches to enhance student motivation in learning